Cyclic response of a precast composite hollow reinforced concrete column using longitudinal rebars and base plate. (14th September 2017) - Cha, Kyung‐Ryul; Seo, Jihye; Kim, Seungjun; Kang, Young‐Jong; Won, Deokhee
Abstract : In this research, the precast segmental construction of composite hollow reinforced concrete (RC) columns was studied. The precast segmental construction of composite hollow RC column requires guidelines for the connections between the bent cap and column segment, connections between column segmental joints, and connections between column segment and footing. The connection methods for different precast composite hollow RC piers were experimentally studied for rational resistance against shear force and bending moments. Two types of precast composite hollow RC columns and cast‐in‐place column were studied in this paper. The performance of these columns was evaluated through experiments. The precast column erected with a base‐plate connection exhibited a performance similar to the cast‐in‐place column.